Updating With Satin Patchwork Technique To Make It Bustier - Nisa, Atina Khoiron; Cahyati, Rika Dwi; Dasining, Dasining; Mu'imamah, Rosita Selvina Putri (Jurnal Tekstil, 2024)
Bustier is underwear that has a function, namely shaping the body to be more proportional. The manufacture of this bustier uses satin patchwork as the main ingredient in its manufacture. Satin fabric is a type of fabric material that is made through a weaving process using the weave technique or filament fiber technique. Patchwork is a craft that combines pieces of patchwork and has different motifs or colors and then becomes a new shape. The manufacture of bustiers that begins with determining the patchwork motif to be used in bustiers, fabric cutting, sewing, during installation, zipper installation, balen, and finishing can produce a bustier that is unique and different from most bustiers in general. In this study, it was stated that the use of patchwork satin fabric can be used in making bustiers.